2000
DOI: 10.1007/978-3-540-40899-4_129
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3D Shape Models of Femoral Articular Cartilage Using Harmonic Maps

Abstract: Abstract. A previous publication has described a method of pairwise 3D surface correspondence for the automated generation of landmarks on a set of examples from a class of shape [3]. However, that method did not guarantee a diffeomorphic correspondence between examples. This affected the model compactness (the ability of the model to capture shape variation in a small number of parameters) and model specificity (the fact that the model will describe shapes only within the class used for training). In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Concerning the establishment of correspondences on the parameter space, approaches similar to ours are those of Brett and Taylor [2] and Meier and Fisher [14]. Both work on a parameter space but do not reduce any distortion.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Concerning the establishment of correspondences on the parameter space, approaches similar to ours are those of Brett and Taylor [2] and Meier and Fisher [14]. Both work on a parameter space but do not reduce any distortion.…”
Section: Related Workmentioning
confidence: 97%
“…A common way to solve this problem is to parameterize every surface to a common base domain and to establish the correspondences on this parameter space. Current work in this context focuses on genus 0 objects such as liver or kidney [2,5,9,14]. Visually spoken, the genus describes the number of holes of a surface.…”
Section: Introductionmentioning
confidence: 99%
“…the MAF problem given in Eq. (2). It is easily shown that the MAF transform is invariant to affine transformations.…”
Section: A Equivalence Of Ica and Mafmentioning
confidence: 99%
“…The Point Distribution Model (PDM) based on PCA of the Active Shape Model (ASM) [1,2] has been succesfully applied to the modelling of the shape of biological objects based on training sets represented by corresponding points. For use for simulation, prediction, or segmentation [3,4,1] a fair number of landmarks are necessary in order to achieve sufficiently good or realistic models.…”
Section: Introductionmentioning
confidence: 99%
“…The practical quality of a PDM relies on the definition of correspondence across a set of segmented samples. Brett and Taylor [3] generated correspondences using ICP while a diffeomorphism between the shapes was maintained by harmonic map. Davies et al [4] solved this problem by manipulating global parameterization subject to the Minimum Description Length (MDL) criterion.…”
Section: Introductionmentioning
confidence: 99%